(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the association between Helicobacter pylori infection and colorectal polyps at Can Tho University of Medicine and Pharmacy Hospital. Methods: A cross-sectional descriptive study was conducted on 337 patients who underwent both upper gastrointestinal and endoscopy and colonoscopy at Can Tho University of Medicine and Pharmacy Hospital from October to December 2025. H.pylori infection was diagnosed using the urease test from gastric mucosal biopsy specimens. Colorectal polyps were confirmed by histopathological examination. Results: The prevalence of H.pylori infection was 21.4%, and the prevalence of colorectal polyps was 30.4%. Polyps were more common in males than in females (37.7% vs 24.2%; OR = 1.900; p = 0.007) and in patients aged ≥ 40 years than in those under 40 years (33.7% vs 17.8%; OR = 2.347; p = 0.009). H.pylori infection was associated with an increased risk of colorectal polyps (45.8% vs. 26.0%; OR = 2.404; p = 0.001). Multivariate analysis identified male sex, age ≥ 40 years, and H.pylori infection as independent factors associated with colorectal polyps. Conclusion: H.pylori infection, male sex, and age ≥ 40 years are independent risk factors for colorectal polyps, highlighting the importance of screening and early detection.